Ramucirumab: the long and winding road toward being an option for mCRC treatment. (4th May 2019) - Debeuckelaere, Celine; Murgioni, Sabina; Lonardi, Sara; Girardi, Noemi; Alberti, Giulia; Fano, Carolina; Gallimberti, Sara; Magro, Cristina; Ahcene-Djaballah, Selma; Daniel, Francesca; Fassan, Matteo; Prenen, Hans; et al.
ABSTRACT: Introduction : Colorectal cancer (CRC) is one of the main causes of cancer-related morbidity and mortality worldwide. Mortality is most often attributable to metastatic disease. Despite the progress achieved so far, life expectancy continues to be limited in most patients. Ramucirumab, a most recent antiangiogenic drug, is vying in the race to metastatic CRC (mCRC) treatment since its approval by the Food and Drug Administration (FDA), based on the results of the RAISE study. Areas covered : This article reviews the role of ramucirumab in mCRC, including clinical indication, safety issues, and future perspectives. Expert opinion : The use of Ramucirumab in clinical practice is still limited, probably due to economic burden and the lack of specific biomarkers. Future efforts will be addressed to improve our knowledge in the use of this drug and better guide us in patients' care.